Phase matrix characterization of long-range-transported Saharan dust using multiwavelength-polarized polar imaging nephelometry - E. Bazo; E. Bazo; D. Pérez-Ramírez; D. Pérez-Ramírez; A. Valenzuela; A. Valenzuela; J. V. Martins; G. Titos; G. Titos; A. Cazorla; A. Cazorla; F. Rejano; et al. (Atmospheric Chemistry and Physics, 2025)
This work investigates scattering matrix elements during different Saharan dust outbreaks over Granada (southeast Spain) in 2022 using a polarized imaging nephelometer (PI-Neph) capable of measuring continuously the phase function (F11) and the polarized phase function (-F12/F11<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="46pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="a6e3f1eb3299ee1cf773cb5249d5f2b9"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-6325-2025-ie00001.svg" width="46pt" height="14pt" src="acp-25-6325-2025-ie00001.png"/></svg:svg>) at three different wavelengths (405, 515 and 660 nm) in the range 5–175°. The focus is on two extreme dust events (PM10 > 1000 µg m−3) in March 2022. During the peaks of these events F11 and -F12/F11<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="46pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="eb7bfb3856e0976d3ae203346717101b"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-6325-2025-ie00002.svg" width="46pt" height="14pt" src="acp-25-6325-2025-ie00002.png"/></svg:svg> show the classical patterns observed for dust samples in laboratory measurements available in the Granada–Amsterdam Light Scattering Database at all wavelengths. However, for the moments prior to and after the peaks the results reveal important sensitivity in -F12/F11<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="46pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="a1251db68b6a7deb25e36c9406ccfa2b"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-6325-2025-ie00003.svg" width="46pt" height="14pt" src="acp-25-6325-2025-ie00003.png"/></svg:svg> at 405 nm. For the other wavelengths, however, this difference in -F12/F11<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="46pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="54ea5d92af68558ddf67c927269fa877"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-6325-2025-ie00004.svg" width="46pt" height="14pt" src="acp-25-6325-2025-ie00004.png"/></svg:svg> is not evident. Moreover, no remarkable changes are found in F11, which is always characterized by strong predominance of forward scattering. The analyses of more frequent and moderate events recorded in summer 2022 (PM10 between 50 and 100 µg m−3) revealed F11 and -F12/F11<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="46pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="d0eb8a74480392a1e8346d3ad295ed0f"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-6325-2025-ie00005.svg" width="46pt" height="14pt" src="acp-25-6325-2025-ie00005.png"/></svg:svg> patterns like those observed prior to and after the extreme events. The combination of PI-Neph measurements with additional in situ instrumentation allowed a typing classification that revealed the peaks in the extreme dust events as pure dust, while for the rest of cases it remarked a mixture of dust with urban background pollution. In addition, simulations with the Generalized Retrieval of Atmosphere and Surface Properties (GRASP) code explain the different patterns in -F12/F11<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="46pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="4b3a52d979b51bf2696ecfd96fa30942"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-6325-2025-ie00006.svg" width="46pt" height="14pt" src="acp-25-6325-2025-ie00006.png"/></svg:svg>, with changes in the refractive indexes and with the different contributions of the fine and coarse mode.